Oxford studies in political philosophy. - Sobel, David; Vallentyne, Pete; Wall, Steven 1967- (Oxford University Press, 2018)
This is the fourth volume of Oxford Studies in Political Philosophy. The series aims to publish some of the best contemporary work in the vibrant field of political philosophy and its closely related subfields, including jurisprudence, normative economics, political theory in political science departments, and just war theory.